2000
DOI: 10.1002/(sici)1097-4636(200005)50:2<171::aid-jbm11>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

In situ gelation of PEG-PLGA-PEG triblock copolymer aqueous solutions and degradation thereof

Abstract: Aqueous solutions of poly(ethylene glycol-b-[DL-lactic acid-co-glycolic acid]-b-ethylene glycol) (PEG-PLGA-PEG) triblock copolymers form a free-flowing sol at room temperature and become a gel at body temperature. In this study, in situ gel formation was investigated in rats. Upon subcutaneous injection of 33 wt % aqueous solutions of PEG-PLGA-PEG triblock copolymer into rats, transparent gels were observed. The gel showed good mechanical strength and the integrity of gels persisted longer than 1 month. The ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 259 publications
(70 citation statements)
references
References 21 publications
1
69
0
Order By: Relevance
“…The combination of hydrophobic/hydrophilic units created a surfactant behavior of the polymers in water, facilitating thus also the solubilization of hydrophobic drugs. In vivo studies showed sufficient mechanical properties and integrity for longer than a month [71]. More recently, Chen et al [72] developed a triblock PLGA-PEG-PLGA-based system for the controlled release of testosterone.…”
Section: Peg/biodegradable Polyester Copolymersmentioning
confidence: 99%
“…The combination of hydrophobic/hydrophilic units created a surfactant behavior of the polymers in water, facilitating thus also the solubilization of hydrophobic drugs. In vivo studies showed sufficient mechanical properties and integrity for longer than a month [71]. More recently, Chen et al [72] developed a triblock PLGA-PEG-PLGA-based system for the controlled release of testosterone.…”
Section: Peg/biodegradable Polyester Copolymersmentioning
confidence: 99%
“…A transparent gel was formed in situ after injection of a 33 wt.-% PEG-PLGA-PEG (550-2810-550) aqueous solution into rats, and gel integrity persisted for one month. [21] Interestingly, thermosensitive hydrogels based on PLGA-PEG-PLGA (BAB-type) (Scheme 3) showed a sol-to-gel transition similar to that of PEG-PLGA-PEG (ABA-type) copolymer hydrogels. [22][23][24] However, the synthetic procedure for BAB-type hydrogels was simpler than that for the ABA-type, using HMDI as a coupling agent.…”
Section: Poly(ethylene Glycol) (Peg)/polyestermentioning
confidence: 99%
“…Recently, novel biodegradable triblock copolymers of polyethylene glycol and poly(lactic/glycolic acid or PEG-PLGA-PEG) were developed by Jeong et al (1997Jeong et al ( , 1999Jeong et al ( , 2000a. Aqueous solutions of these copolymers exhibit sol-to-gel transition at body temperature.…”
Section: Thermoreversible Gelsmentioning
confidence: 99%